The role of microfinance institutions in job creation - Tmava, Qazim; Bellaqa, Bashkim (Edelweiss Applied Science and Technology, 2025)
The primary objective of this research is to assess the influence of Micro Financial Institutions (MFIs) on job creation in Kosovo by examining the relationships between MFI microcredits, consulting services, government coordination, interest rates, and so on. According to the September 2024 status, Kosovo's microfinance sector consists of 9 MFIs and 23 Non-Banking Financial Institutions (NBFIs). The findings of the linear regression analysis suggest that there is a weak relationship between the volume of microcredits granted by MFIs and the creation of new jobs, with p = 0.042, which is slightly lower than the significance value of 0.05. The MFI consultancies, MFI programs, and high interest rates of MFI microcredits show a substantial negative link with employment creation. The parameter β values are smaller than the values of p. Methodologically speaking, apart from secondary data, a survey connected to the purpose of the research was also conducted. MFIs have a number of challenges in creating jobs, including a lack of entrepreneurial training and financial skills, low institutional capacity, high interest rates, and so on. The study recommends that policy and strategy makers in Kosovo maximize job creation through MFIs by implementing an integrated approach.